Kebudayaan Onsen dan Eksistensinya di Jepang - Reny Wiyatasari (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
Japan is known to have a culture that dates back hundreds of years, namely the culture of bathing in an onsen. Japanese people get excited when they soak in the onsen. They are even willing to go far to satisfy their desire to soak in an onsen. Japanese people go to onsen for a variety of purposes, including healing, relaxing the body and mind, and also as a means of gathering for relationships familiarity and communication. Therefore, it is not surprising that businesses that take advantage of onsen are still able to exist today. Onsen-ryokou or traveling to enjoy hot springs is one of the most potential tourism in Japan. Data were collected through literature study and inteviews. This study focused on factors that led to the ongoing onsen business today. The result showed that the onsen business can survive due to four factors, including : 1) Japanese geographical conditions, 2) Japanese season charateristics, 3)Benefit of onsen for the body, and 4) Onsen is part of Japanese culture